2001
DOI: 10.1128/mcb.21.10.3289-3301.2001
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast Rad17 Associates with Chromatin in Response to Aberrant Genomic Structures

Abstract: Fission yeast checkpoint protein Rad17 is required for the DNA integrity checkpoint responses. A fraction of Rad17 is chromatin bound independent of the other checkpoint proteins throughout the cell cycle. Here we show that in response to DNA damage induced by either methyl methanesulfonate treatment or ionizing radiation, increased levels of Rad17 bind to chromatin. Following S-phase stall induced by hydroxyurea or a cdc22 mutation, the chromatin-bound Rad17 progressively dissociates from the chromatin. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…The checkpoint responses in S. pombe require a group of six "checkpoint Rad proteins" (Rad1, Rad3, Rad9, Rad17, Rad26, and Hus1) that are thought to function as sensors of DNA replication arrest and DNA damage (11). Rad1, Rad9, and Hus1 have weak sequence similarities to proliferating cell nuclear antigen and form a ring-shaped complex (12,31,38). Rad17 has sequence similarity to replication factor C (RFC) proteins (32) and associates with other RFC subunits (38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The checkpoint responses in S. pombe require a group of six "checkpoint Rad proteins" (Rad1, Rad3, Rad9, Rad17, Rad26, and Hus1) that are thought to function as sensors of DNA replication arrest and DNA damage (11). Rad1, Rad9, and Hus1 have weak sequence similarities to proliferating cell nuclear antigen and form a ring-shaped complex (12,31,38). Rad17 has sequence similarity to replication factor C (RFC) proteins (32) and associates with other RFC subunits (38).…”
mentioning
confidence: 99%
“…Rad1, Rad9, and Hus1 have weak sequence similarities to proliferating cell nuclear antigen and form a ring-shaped complex (12,31,38). Rad17 has sequence similarity to replication factor C (RFC) proteins (32) and associates with other RFC subunits (38). The RFC complex recruits proliferating cell nuclear antigen onto DNA; therefore, it has been proposed that the Rad17 complex loads a Rad1-Rad9-Hus1 complex onto sites of DNA damage.…”
mentioning
confidence: 99%
“…A second potential DNA-targeting subunit is Rad17 (S. pombe nomenclature). In fission yeast, rad17 + associates with chromatin throughout the yeast cell cycle, and this basal level of DNA-bound rad17 + is either increased or decreased in response to genotoxic stress, with the direction of change determined by the type of DNA damage incurred by these cells (Griffiths et al 2000;Kai et al 2001). In addition to its predicted role as a checkpoint clamp loader for the Rad1-Rad9-Hus1 complex (Thelen et al 1999;Venclovas and Thelen 2000), our group has shown that treatment of human cells with genotoxic agents triggers rapid associations of ATM and ATR with hRad17 (Bao et al 2001).…”
Section: +mentioning
confidence: 99%
“…Interestingly, proteins that bind to components of nuclear matrix such as lamin B1 (Luderus et al, 1992), centromere proteins (Payen et al, 1998), and RAD17 homolog (Kai et al, 2001) were also identified. A subset of these proteins may represent proteins that interact with the nucleophosmin component of the NPM-ALK fusion protein.…”
Section: Unique Proteins Identified By Alk Immunoprecipitationmentioning
confidence: 99%